2018
DOI: 10.1002/jcb.27503
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐125a suppresses cell migration, invasion, and regulates hyaluronic acid synthase 1 expression by targeting signal transducers and activators of transcription 3 in renal cell carcinoma cells

Abstract: Renal cell carcinoma (RCC) is one of the most common cancers in urology. MicroRNA-125a (miR-125a) has been demonstrated to be implicated in various cancers. However, the functional role of miR-125a in RCC remains largely unclear. This study was aimed to investigate the functional role of miR-125a and the expression relevance of signal transducers and activators of transcription 3 (STAT3) with hyaluronic acid synthase 1 (HAS1) in RCC. We revealed that miR-125a was downexpressed in 786-O cells, and examined tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It has been reported in several cancers that the antitumor effect of miR125a-5p is associated to STAT3 inhibition. For example, miR-125a promotes paclitaxel sensitivity through inhibiting STAT3 expression in cervical cancer [22], gastric cancer cells [23], and renal cancer [24]. The current study con rmed that STAT3 pathway was down-regulated by miR125a-5p, as revealed by IPA analysis, website prediction, luciferase reporter assay, PCR and western blotting.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported in several cancers that the antitumor effect of miR125a-5p is associated to STAT3 inhibition. For example, miR-125a promotes paclitaxel sensitivity through inhibiting STAT3 expression in cervical cancer [22], gastric cancer cells [23], and renal cancer [24]. The current study con rmed that STAT3 pathway was down-regulated by miR125a-5p, as revealed by IPA analysis, website prediction, luciferase reporter assay, PCR and western blotting.…”
Section: Discussionsupporting
confidence: 67%
“…In recent years, an increasing number of researchers have focused on the relationship between tumorigenesis and HAS1 and showed the role of HAS1 in the growth of RCC and other malignant tumors [ 92 ]. The results of Mao-Kun Sun et al showed that miR-125a could inhibit RCC cell migration and invasion by targeting STAT3 to regulate the expression of HAS1 [ 93 ]. In summary, the abnormal expression of PGs in tumor cells might be used as a marker for cancer progression and patient.…”
Section: Proteoglycansmentioning
confidence: 99%
“…3 A). While there are other HAS enzymes (HAS2 and HAS3), HAS1 has been shown to be associated with cell migration and invasion in renal carcinoma cells [26] . The cells were subcloned by serial dilution in 96-well plates, and single colonies were subcultured.…”
Section: Resultsmentioning
confidence: 99%